The workforce composition of young firms and product innovation: Complementarities in the skills of founders and their early employees - Bettina Müller; Martin Murmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We investigate the extent to which complementarities between technical and business skills of founders and employees matter for the generation of market novelties by new ventures. Using data about German start-ups, we find that there are no complementarities between technical and business skills within the group of founders, but that there are significant complementarities between technically trained founders and employees who have business skills. This suggests that the innovation potential of start-ups by technically trained founders is best explored by hiring employees who are trained in business. However, a reverse relationship does not exist: There are no complementarities between founders with business skills and employees with technical skills.
urn:nbn:de:bsz:180-madoc-415639
Keywords: J24; L23; L26; M13; M51; Q31; 330; Entrepreneurship; Innovation; Human Capital; Skills; Complementarity